Determinasi Keputusan Pembelian Generasi Z Terhadap Produk Somethinc di Shopee Berbasis AI di Surakarta - Wahyu Triantara; Ida Aryati; Istiatin Istiatin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid development of e-commerce has encouraged intensive use of Artificial Intelligence (AI) in influencing consumer decision-making processes, especially Generation Z as digital natives. This research aims to analyze the influence of content quality, personalization and AI-based interactivity on purchasing decisions for Somethinc products on the Shopee platform by Generation Z in Surakarta City. This research uses a quantitative approach by collecting data through questionnaires to 100 respondents, which are analyzed using multiple linear regression. The research results show that AI-based personalization and interactivity have a significant influence on purchasing decisions, while content quality does not show a direct significant influence. These findings indicate that for Generation Z, a relevant and interactive shopping experience is more decisive than the quality of content which tends to be perceived as a basic standard. This research contributes to the digital marketing literature by confirming the shifting role of AI-based marketing elements in shaping Generation Z purchasing behavior on e-commerce platforms.